Eye-safe 1.55 μm high-repetition-frequency self-Q-switched Er:Yb:Lu2Si2O7 pulse laser. (January 2021) - Chen, Yujin; Huang, Jianhua; Lin, Yanfu; Gong, Xinghong; Luo, Zundu; Huang, Yidong
Highlights: An eye-safe 1.55 μm self- Q -switched pulse laser was firstly demonstrated. 1.55 μm pulse lasers with 40–240 kHz repetition frequency were realized. Self- Q -switching can obtain conveniently a high-repetition-frequency 1.55 μm laser. Abstract: An eye-safe 1.55 μm solid-state pulse laser with high repetition frequency is useful for some applications such as lidar. A high-repetition-frequency self- Q -switched 1.55 μm pulse laser was firstly demonstrated in an Er:Yb:Lu2 Si2 O7 crystal end-pumped by a continuous-wave 975 nm diode laser. The influences of various cavity parameters on the self- Q -switched pulse laser performance were investigated. At an absorbed pump power of 6.3 W and a pump beam diameter of 400 μm, a self- Q -switched 1.55 μm pulse laser with energy of 3.37 μJ, repetition frequency of 43 kHz, and duration of 1.04 μs was realized. When the pump beam diameter was changed to 100 μm, the repetition frequency and duration of the pulse laser increased to 230 kHz and decreased to 236 ns, respectively, while the pulse energy reduced to 1.22 μJ.